2020
DOI: 10.3390/biom11010034
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Treatment with Vitamins C and B2 for Methotrexate-Induced Gastrointestinal Mucositis

Abstract: Mucositis is a common side-effect of chemotherapy treatment, inducing alterations in the composition of the gut microbiota. Redox active compounds, such as vitamins B2 and C, have been shown to reduce inflammation and enhance the growth of anaerobic bacteria in the gut. We therefore aimed to (1) validate the ability of these compounds to promote bacterial cell growth in vitro, and (2) determine their prophylactic efficacy in a rat model of methotrexate (MTX)-induced mucositis. Bacterial growth curves were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Muribaculaceae (S24-7) is a typical rodent bacterial family belonging to the Bacteroidetes phylum already documented to regulate FMT efficacy in rodents [49]. It is recognised to increase in abundance after prebiotic intervention with vitamin B2 18 and selenium [50], both of which have documented benefits in the prevention of mucosal injury caused by chemotherapy [18,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muribaculaceae (S24-7) is a typical rodent bacterial family belonging to the Bacteroidetes phylum already documented to regulate FMT efficacy in rodents [49]. It is recognised to increase in abundance after prebiotic intervention with vitamin B2 18 and selenium [50], both of which have documented benefits in the prevention of mucosal injury caused by chemotherapy [18,51].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been demonstrated that FMT is able to restore the microbial community after 5-fluorouracil and antibiotics [17], it remains unclear if FMT-induced microbial restoration is able to prevent or minimise MBI and its associated clinical manifestations. The present study therefore aimed to determine the impact of microbial manipulation, using antibiotics and FMT, on MBI and its clinical manifestations using a validated model of methotrexate-induced gastrointestinal toxicity [18,19]. By delivering autologous gut microbes after chemotherapy, we aimed to provide new data to aid in defining the causal contribution of the microbiome to MBI and associated symptoms and identify translational methods aimed at strengthening the host microbiome before treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of anaerobic bacteria Blautia coccoides , R. intestinalis and Enterococcus faecalis was stimulated by vitamin B2 in vitro ( 68 ). Replenishment of vitamin B2 has been reported to alter the composition and β diversity of gut microbiota in mice ( 69 ).…”
Section: Vitamin B2mentioning
confidence: 99%
“…Yilmaz et al [ 213 ] reported the beneficial effect of daily use of vitamin supplement injections to ameliorate intestinal inflammation and protect rats against MTX-induced mucositis. Vitamin C and B2 efficacy has been tested by da Silva Ferreira et al [ 214 ] using an in vitro bacterial growth model, and an in vivo rat model. Both vitamins were able to enhance the growth of gut bacteria, leading to enrichment of Blautia coccoides and Roseburia intestinalis.…”
Section: Nutraceuticals Use To Counteract Mtx Toxicity In Experimenta...mentioning
confidence: 99%
“…Both vitamins were able to enhance the growth of gut bacteria, leading to enrichment of Blautia coccoides and Roseburia intestinalis. However, despite the fact that vitamin C ameliorated clinical symptoms of mucositis, neither of the vitamins was able to modulate the course of MTX-induced mucositis, as assessed by citrulline plasma levels [ 214 ].…”
Section: Nutraceuticals Use To Counteract Mtx Toxicity In Experimenta...mentioning
confidence: 99%